THE APPLICATION OF CONTEXTUAL TEACHING AND LEARNING IN TEACHING ELLIPTICAL SENTENCES TO THE GRADE NINE STUDENTS OF SMP NEGERI 17 PALU - Putri Ningtyas (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
The Application of Contextual Teaching and Learning in Teaching Elliptical sentences to the Grade Nine Students of SMP Negeri 17 Palu. The objective of this research was to prove that the application of contextual teaching and leraning (CTL) can improve the ability of the grade nine students in constructing elliptical sentences. The sample of the research was taken by using cluster random sampling technique. Class IX B was the experimental class while IX C was the control class. The instruments used to collect the data were observation and tests. The results of observation were analyzed by using descriptive analysis. The results of tests were analyzed by applying statistic analysis. Applying 0.05 level of significance and 56 (29+29-2) degree of freedom (df), the writer found that t-test value (6.136) was greater than t-table value (2.007). It means that the application of contextual teaching and learning is effective to improve students’ ability in constructing elliptical sentences.